Formação de professores de português como língua adicional para a educação a distância no Amazonas - (:unkn) unknown (Universidade Federal do Amazonas, 2024)
This research aims to investigate the essential aspects of teacher training for teaching Portuguese as an Additional Language (PAL) for the context of Distance Education (DE) in Amazonas/AM, based on the emerging factors that contribute to the increase in demand of this type of teaching, referring to the teaching of PAL, the growing access to Digital Information and Communication Technologies (DICTs) and, consequently, teaching technological literacy. Understanding the roles of culture, context and beliefs built on this type of teaching, formed by teachers, it was possible to outline the directions related to the analysis of this training process linked to the theoretical foundations presented in the analyzed literature, which are expanded throughout the dissertation. The methodological procedures are based on the work of Savin-Baden and Major (2013), focusing on the thematic work of qualitative research, and Paiva (2019), exploring concepts about research, aiming to meet the proposed and essential objectives for understanding the formation of PAL teachers for the distance learning context. From this, with an analysis of the Pedagogical Course Projects (PCP) of the State University of Amazonas (UEA) and Federal University of Amazonas (UFAM) and interviews carried out with teachers in the PLA area, who have already worked or work in the distance context, it will be possible to carry out an analytical survey of the undergraduate training process. So that from this, it is possible to indicate possible and necessary paths for training teachers in this area of teaching for the distance learning context
Training Portuguese teachers as an additional language for distance education in Amazonas
Keywords: Ensino à distância; Professores de português - Formação; Prática de ensino; LINGUISTICA, LETRAS E ARTES; Português como língua adicional; Formação de professores; Educação a distância; Alfabetização tecnológica docente